Geoknife: reproducible web‐processing of large gridded datasets. Issue 4 (9th November 2015) - Read, Jordan S.; Walker, Jordan I.; Appling, Alison P.; Blodgett, David L.; Read, Emily K.; Winslow, Luke A.
Abstract : Geoprocessing of large gridded data according to overlap with irregular landscape features is common to many large‐scale ecological analyses. The geoknife R package was created to facilitate reproducible analyses of gridded datasets found on the U.S. Geological Survey Geo Data Portal web application or elsewhere, using a web‐enabled workflow that eliminates the need to download and store large datasets that are reliably hosted on the Internet. The package provides access to several data subset and summarization algorithms that are available on remote web processing servers. Outputs from geoknife include spatial and temporal data subsets, spatially‐averaged time series values filtered by user‐specified areas of interest, and categorical coverage fractions for various land‐use types.